Knowledge, Attitudes, and Practices Towards Vitamin D Deficiency During the COVID-19 Pandemic in Saudi Arabia: A Cross-Sectional Study - Huda Wazzan; Manal Malibary (International Journal of Food and Nutritional Health, 2026)
Vitamin D plays a crucial role in bone health and various physiological functions, yet deficiency remains a global public health concern. This study aimed to assess knowledge, attitudes, and practices (KAP) related to vitamin D among adults in Saudi Arabia, with a particular focus on gender differences and the impact of the COVID-19 pandemic. A cross-sectional survey was conducted among 449 participants. Knowledge was as-sessed through nine questions, with scores ranging from 0 to 26. Attitudes were measured using three ques-tions. Participants were categorized into good or poor knowledge, attitude, and practice groups, and statistical analyses were conducted to examine associations with demographic factors. The mean knowledge score was 14.1 ± 3.9, while attitude and practice scores were low (1.2 ± 0.89 and 10.29 ± 3.86, respectively), indicating poor concern and behaviours related to vitamin D. Females showed greater knowledge and more health-related actions (e.g., supplement use, testing), whereas males reported better intake of vitamin D-rich foods (p < 0.001). Despite high knowledge, attitudes and practices need to improve across participants. most group differences in vitamin D-related KAP were not significant, except for citizenship, where non-Saudis showed better practices and slightly lower attitude scores than Saudis. The findings highlight the need for targeted public health initiatives to improve awareness of dietary sources, promote appropriate sun exposure, and en-courage proactive vitamin D supplementation and testing, particularly among groups at higher risk of defi-ciency.